Musical Objects, Cross-Domain Correspondences, and Cultural Choice: Commentary on “Cross-Cultural Representations of Musical Shape” by George Athanasopoulos and Nikki Moran - Eitan, Zohar (Empirical Musicology Review, 2013)
The target article illustrates deep cross-cultural gaps, involving not only the representation of musical shape but also the notion of a musical object itself. Yet, numerous empirical findings suggest that important cross-modal correspondences involving music and visual dimensions are inborn or learned at infancy, prior to the acquisition of language and most culture-specific behavior. Drawing on recent empirical work, the commentary attempts to reconcile this apparent disparity.